Assessment of the microbiological quality and safety of minimally processed vegetables sold in Piracicaba, SP, Brazil. (1st August 2020) - Santos, T.S.; Campos, F.B.; Padovani, N.F.A.; Dias, M.; Mendes, M.A.; Maffei, D.F.
Abstract: : Significance and Impact of the Study: In this study, the microbiological quality and safety of minimally processed vegetables sold in the city of Piracicaba, SP, Brazil, were evaluated through the detection of Salmonella spp., generic Escherichia coli and other Enterobacteriaceae . The results obtained point to poor microbiological quality and safety of a few samples, as generic E. coli was detected in 16 out of 100 samples and Salmonella was isolated from one of them. This indicates hygiene failures during their processing and health risk to consumers, since these products are usually sold as ready‐to‐eat and typically require no further heat treatment before consumption. The present study shows the results of the microbiological quality and safety of minimally processed vegetables sold in supermarkets and grocery stores located in the city of Piracicaba, SP, Brazil. A total of 100 samples were collected and submitted to enumeration of total coliforms, coliforms at 45°C and generic Escherichia coli using the standard most probable number (MPN) method, in addition to enumeration of total Enterobacteriaceae by plating on MacConkey agar. Moreover, colonies of Enterobacteriaceae were randomly selected and submitted to identification on a MALDI‐TOF MS Biotyper™. Samples were also tested for Salmonella spp. according to the ISO 6579:2002 method. The mean count of total coliforms was 2·9 ± 0·5 log MPN per g. For coliforms at 45°C, 20 samples were positive (mean 1·5 ± 1·0 log MPN per g). Generic E. coli was detected in 16 samples (mean 1·4 ± 0·9 log MPN per g) and only one was positive for Salmonella . The mean count of total Enterobacteriaceae was 6·5 ± 1·2 log CFU per g and the most frequent genera identified by MALDI‐TOF were Enterobacter (25·9%), Pantoea (9·6%) and Rahnella (9·0%). Overall, results point to poor microbiological quality of a few samples, indicating hygiene failure during their processing. This can pose health risks to consumers, mainly because these products were labelled as sanitized and marketed as ready‐to‐eat. Significance and Impact of the Study: In this study, the microbiological quality and safety of minimally processed vegetables sold in the city of Piracicaba, SP, Brazil, were evaluated through the detection of Salmonella spp., generic Escherichia coli and other Enterobacteriaceae . The results obtained point to poor microbiological quality and safety of a few samples, as generic E. coli was detected in 16 out of 100 samples and Salmonella was isolated from one of them. This indicates hygiene failures during their processing and health risk to consumers, since these products are usually sold as ready‐to‐eat and typically require no further heat treatment before consumption.